C677T Polymorphism in the MTHFR Gene Is Associated With Risperidone-Induced Weight Gain in Schizophrenia - Liao, Jingping; Wang, Ning; Ma, Mengying; Lu, Tianlan; Yan, Hao; Yue, Weihua (Frontiers in Psychiatry, 2020)
Objective: To explore the association of methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism with risperidone-induced weight gain. Methods: We analyzed the association between MTHFR C677T polymorphism and risperidone-induced weight gain in 356 schizophrenia patients. The patients were treated with risperidone for 8 weeks. The height and body weight of the patients were measured before and 8 weeks after risperidone treatment. Blood DNA was genotyped for MTHFR C677T polymorphisms. Results: We found a significant association between MTHFR C677T polymorphism and body mass index (BMI) change after 8-week risperidone treatment. The BMI of carriers with different genotypes of MTHFR gene increased over 2-8 weeks. After 8 weeks of risperidone treatment, BMI added value (kg/m2) of CC or CT genotype carriers was significantly higher than that of TT genotype carriers [CC (4.47 ± 1.09), CT (4.54 ± 1.27), TT (2.31 ± 0.75), F = 5.634, P = 0.001]. Based on whether the rate of weight gain from baseline at 8 weeks of treatment exceeded 7%, it was divided into a weight gain group (n = 61) and a non-weight gain group (n = 295). The C allele frequency was significantly different between the two groups (48.4 % vs 32.4%, 2 = 11.342, P = 0.001). Conclusion: MTHFR C677T polymorphism was associated with risperidone-induced weight gain in Chinese Han population.